Molecular Diversity of Sapovirus Infection in Outpatients Living in Nanjing, China (2011–2013) - Hong-ying Zhang; Meng-kai Qiao; Xuan Wang; Min He; Li-min Shi; Guo-xiang Xie; Hei-ying Jin (Gastroenterology Research and Practice)
Aim. To gain insight into the molecular diversity of sapovirus in outpatients with acute gastroenteritis in Nanjing, China. Methods. The specimens from outpatients clinically diagnosed as acute gastroenteritis were detected by real-time PCR; RT-PCR was then performed to amplify part of VP1 sequences. The PCR products were cloned into pGEM-T Easy vector and bidirectionally sequenced. All sequences were edited and analyzed. A phylogenetic tree was drawn with the MEGA 5.0 software. Results. Between 2011 and 2013, 16 sapovirus positive cases were confirmed by real-time PCR. The infected cases increased from two in 2011 and six in 2012 to eight in 2013. The majority was children and the elderly (15, 93.75%) and single infections (15, 93.75%). Of the 16 real-time positive specimens, 14 specimens had PCR products and the analysis data of the 14 nucleic sequences showed that there was one GI genogroup with four genotypes, two GI.2 in 2011, three GI.2, and one GI.1 in 2012 and one GI.2, three GI.1, two GI.3, and two GI.5 in 2013. Conclusion. Our data confirmed continuous existing of GI genogroup and GI.2 genotype from 2011 to 2013 in Nanjing and the successive appearance of different genotypes from outpatients with gastroenteritis.